Learning from farmers for improved climate services - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Live report at COP18 from CGIAR Research Program on Climate Change, Agriculture and Food Security https://ccafs.cgiar.org Farmers need good climate information so that they can make decisions in a changing climate. But scientists should listen to them before designing information products, say Dr Arame Tall and Kalpana Venkatasubramanian of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). Interview filmed at the UN Climate Talks in Doha, Qatar. 1 December 2012.